Increase in the Posterior Tibial Slope Provides Better Joint Awareness and Patient Satisfaction in Cruciate-Retaining Total Knee Arthroplasty - Ogawa, Hiroyasu; Sengoku, Masaya; Nakamura, Yutaka; Shimokawa, Tetsuya; Ohnishi, Kazuichiro; Akiyama, Haruhiko (The Journal of Knee Surgery, 2023)
The effect of the posterior tibial slope (PTS) in cruciate-retaining total knee arthroplasty (CR-TKA) on clinical outcomes remains unclear. We aimed to investigate (1) the effect of alteration of the PTS on clinical outcomes, including patient satisfaction and joint awareness, and (2) the relationship between the patient-reported outcomes, the PTS, and compartment loading. Based on the alteration of the PTS after CR-TKA, 39 and 16 patients were stratified into increased and decreased PTS groups, respectively. Clinical evaluation was performed by the Knee Society Score (KSS) 2011 and the Forgotten Joint Score-12 (FJS-12). Compartment loading was intraoperatively assessed. KSS 2011 (symptoms, satisfaction, and total score) was significantly higher (p = 0.018, 0.023, and 0.040, respectively), and FJS (“climbing stairs?”) was significantly lower (p = 0.025) in the increased PTS group compared with the decreased PTS group. The decrease in both medial and lateral compartment loading of Δ45°, Δ90°, and ΔFull was significantly greater in the increased PTS group than in the decreased PTS group (p< 0.01 for both comparisons). Medial compartment loading of Δ45°, Δ90°, and ΔFull significantly correlated with KSS 2011 for “symptom” (r = − 0.4042, −0.4164, and −0.4010, respectively; p = 0.0267, 0.0246, and 0.0311, respectively). ΔPTS significantly correlated with medial compartment loading differentials of Δ45°, Δ90°, and ΔFull (r = − 0.3288, −0.3792, and −0.4424, respectively; p = 0.0358, 0.01558, and 0.0043, respectively). Patients with increased PTS showed better symptoms and higher patient satisfaction compared with those with decreased PTS following CR-TKA, possibly due to a greater decrease in compartment loading during knee flexion.Level of evidence:level IV, therapeutic case series.
Keywords: posterior tibial slope; joint awareness; patient satisfaction; total knee arthroplasty; compartment loading